2016
DOI: 10.1016/j.canep.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breast cancer risk associated with tea consumption by menopausal and estrogen receptor status among Chinese women in Hong Kong

Abstract: Tea or green tea drinking was not associated with overall breast cancer risk, which may be masked by the differential effect in pre- and post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The association between tea consumption and decreased risk of breast cancer was also confirmed by population-based case-control studies carried out in China [10,12,17], the USA [18,19,20], and Singapore [21,22]. There were studies showing that green tea consumption significantly reduced the risk of breast cancer [18] and the women who drank three or more cups of tea per day had a 37% reduced breast cancer risk than their counterparts that did not drink tea [20].…”
Section: Epidemiological Evidencementioning
confidence: 68%
“…The association between tea consumption and decreased risk of breast cancer was also confirmed by population-based case-control studies carried out in China [10,12,17], the USA [18,19,20], and Singapore [21,22]. There were studies showing that green tea consumption significantly reduced the risk of breast cancer [18] and the women who drank three or more cups of tea per day had a 37% reduced breast cancer risk than their counterparts that did not drink tea [20].…”
Section: Epidemiological Evidencementioning
confidence: 68%
“…The quality of 10 case‐control studies was assessed, and it was observed that all of these studies had a NOS score ≥ 7 (Inoue et al, ; Iwasaki et al, ; Iwasaki, Inoue, Sasazuki, Miura, et al, ; Lee et al, ; Li et al, ; Mizoo et al, ; Shrubsole et al, ; Wang et al, ; Wu, Tseng, Van Den Berg, & Mimi, ; Zhang et al, ); however, one of the studies had not performed adequate adjustments for confounding variables and was not included in the meta‐analysis (Lee et al, ). Moreover, the quality of four cohort studies was assessed; all these studies had a NOS score ≥ 7 and were included in the meta‐analysis (Dai et al, ; Iwasaki, Inoue, Sasazuki, Miura, et al, ; Key et al, ; Suzuki et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that GT drinking is associated with a reduced risk of breast cancer among premenopausal women but it is surprisingly associated with an increased risk among postmenopausal women. It has been suggested that GT effects might be modified by estrogen receptors (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations